Efektivitas Ekstrak Etanol Kulit Buah Terung Ungu (Solanum melongena L.) sebagai Antimalaria terhadap Jumlah Eosinofil pada Mencit (Mus musculus) yang Diinduksi Plasmodium berghei - Haris, Muhammad Faisal; Kahtan, Muhammad Ibnu; Widiyantoro, Ari (Fakultas Farmasi Universitas Andalas, 2020)
Malaria is a disease caused by Plasmodium that is transmitted to humans through female Anopheles mosquito bite. Many cases of antimalarial drug resistance such as chloroquine led to the need for new antimalarial discoveries. Eggplant contains many secondary metabolites that are potential as antimalarial. This study aimed to determine the effectivity of ethanol extract of eggplant peels as antimalarial towards eosinophil in mice induced by Plasmodium berghei. Eggplant peels were extracted by maceration method using 70% ethanol. The analysis of secondary metabolites from the ethanol extract of eggplant peels was conducted using tube test and thin layer chromatography. The percentage of parasitemia and eosinophil were calculated from peripheral blood smear of mice which were treated with extracts at the doses of 0.075, 0.15, and 0.30 mg/20 g of body weight. Dihydroartemisinin-piperaquin (3.744 mg/20 g of body weight) was used as positive control, while distilled water was used as negative control. The study showed that ethanolic extract of the eggplant peels contained alkaloids, flavonoids, terpenoids, steroids, phenolic, and saponins. The extract effectively reduced parasitemia at a dose of 0.075 mg/20 g, but it was not effective in increasing the number of eosinophil in mice. There was no correlation between the number of parasitemia and eosinophil. The study concludes that ethanolic extract of the eggplant peels exhibits antimalarial activity, but does not show immunomodulatory activity in increasing eosinophil.